Primary mediastinal seminoma achieved by transbronchial mediastinal cryobiopsy - Zhang, Jing; Fu, Wan-Lei; Huang, Zan-Sheng; Guo, Jie-Ru; Li, Qi; Herth, Felix; Fan, Ye (Respiration, 2020)
Mediastinal biopsy is essential for the clinical diagnosis of mediastinal disease. Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) is a well-established approach for obtaining diagnostic samples from mediastinal masses or enlarged lymph nodes which is proven to be minimally invasive and effective. However, the insufficiency of intact samples acquired might restrict the diagnostic efficacy of EBUS-TBNA for mediastinal lesions such as rare malignancy and granulomatous disorder. We here present an EBUS-guided approach for the cryobiopsy of mediastinal diseases that is capable of providing larger amounts of intact tissue with few observed complications.